HEIDEGGER ABOUT THE ANTHROPOLOGICAL INTENTION OF DESCARTES` PHILOSOPHIZING - Anatolii M. Malivskyi (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen', 2013)
The purpose of the article is to single out and comprehend the key points of Heidegger`s vision of the main ideas of Descartes` philosophy while searching «the other beginning» of philosophizing as anthropology. The implementation of the objective assumes the solution of the following tasks: justification of the Heidegger`s idea of the critical relation to the established stereotypes of technomorphism about the basic intention of Descartes` philosophy, the reconstruction of the context of Heidegger`s considering the understanding of the basic intention and main motives of Descartes` philosophizing, the authenticity analysis of the reception of Descartes` doctrine by Heidegger in modern literature. Methodology. The achievements of the anthropologically focused thought of the 20th century, namely existentialism, philosophical anthropology, personalism, communicative philosophy have the essential potential during the constructive judgment and theoretical reconstruction of anthropological intention of philosophizing. Heidegger's heritage takes on a special significance, especially his reflections about the ways of searching and finding a substantial alternative to the technicism in the form of «the other beginning» of philosophizing. Scientific novelty. The analysis of the scientific literature, devoted to the relationship of Heidegger – Descartes, testifies to the domination of the truncated understanding of Descartes`s philosophy deprived of an anthropological component, and, as a result, ignoration of the substantial succession of the Descartes` ideas by Heidegger. Considering Heidegger's corresponding texts devoted to the understanding of the deep transformations of the New time, we find out the anthropology as a cornerstone of science and technology. Understanding the basic part of anthropology in the culture of the New time makes Heidegger devote much attention to the destruction of the established ideas of self-sufficiency of science, technology, thinking and to the detection of those hidden ones from a superficial view of personal nature of philosophical knowledge. Conclusions. Heidegger reasonably decides to pay much attention to Descartes` heritage as one of the fundamental thinkers, whose works are especially important during the simultaneous understanding of both the sources of the European anthropology, and the formation of the bases of the technogenic civilization of the New time. Heidegger's heritage considerably contributes to more authentic interpretation of the basic intention and the main motives of Descartes` philosophy. His opening new prospects to a considerable degree is caused by his own anthropological orientation, critical attitude to the linear concept of the history of philosophy, the rejection of superficial teсhnomorphism interpretation of philosophy.